(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The works "Devoni Lug’otit Turk" and "Kutadgü Bilig" are two seminal texts written in the Turkic languages that provide invaluable insights into the linguistic practices and phraseology of their time. Written centuries apart, a comparative analysis of phrases used in these works can shed light on the evolution of the Turkic languages as well as cultural influences. This article will conduct such a comparative study with a focus on identifying commonalities and differences in phrases related to various topics such as governance, society, religion and nature.